Walking between grooves in the ground, learning from the peasant visualities - Leandro de Souza Silva; Paulo Pires de Queiroz (Revista Brasileira de Educação do Campo)
Peasant visualities emerge as a field of disputes, constituting aesthetic and educational practices that challenge hegemonic narratives about the rural environment. Like furrows in the ground, they bear the marks of popular knowledge, resistance and the imagination of life. Following this path, the objective of this study is to understand how visualities in the Zumbi dos Palmares settlement (RJ) contribute to aesthetic-educational processes within his spatiality. To achieve this, a theoretical-conceptual dialogue is proposed, integrating studies in Visual Culture, Spatialities, and Popular Culture and Education, combined with an exercise in reading visualities collected in the field. The participatory methodology enabled data collection and guided the discussion, revealing the settlement's spatiality as a territory of resistance, creation, and aesthetic invention. The results of the research show that peasant visualities contribute to the aesthetic-educational formation of the people involved in the life of the settlement, at the same time as they challenge and reconfigure dominant discourses on culture and education in rural areas. Thus, the research reaffirms the relationship between visual culture and popular education in the construction of counter-hegemonic epistemologies that enhance the autonomy and resistance of people in the countryside.